IMPLEMENTASI COOPERATIVE LEARNING DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA PENDIDIKAN TINGKAT DASAR - Rosyid, Moh. Zaiful (Reflektika, 2024)
AbstractThis study aims to explore the application and impact of cooperative learning in increasing students' learning motivation at Madrasah Ibtidaiyah Sabilul Muttaqien Buddagan Pamekasan. This research uses a qualitative approach with a field research method, where data is collected through observation, in-depth interviews, and documentation. The results show that the application of Cooperative Learning in this madrasah involves several approaches that are tailored to the students' conditions, including Jigsaw and Think-Pair-Share. The implementation of cooperative learning has a positive impact on students' intrinsic motivation and extrinsic motivation. Students become more actively involved in the learning process, experience increased self-confidence, and show better cooperation skills with their classmates. In addition, the findings also indicated implementation challenges, such as different levels of student engagement, time management, and diverse academic abilities within the groups. However, through adjustments in learning strategies, such as clearer role setting and intensive guidance from teachers, these obstacles can be overcome.